ANALISIS PEMANFAATAN SUMBER PEMBELAJARAN DARING PADA MASA COVID-19 PADA PEMBELAJARAN EKONOMI SMA ISLAMIYAH PONTIANAK - Sindi Septiani; Bambang Genjik; Okianna Okianna (Universitas Tanjungpura, 2022)
This study aims to find out how to utilize learningresources during the COVID-19 pandemic at SMAIslamiyah Pontianak. This research uses qualitativeresearch with descriptive type. The source of the datain this research is the teacher of economics at SMAIslamiyah Pontianak. Data collection techniques inthis study were taken through the results ofobservations and interviews conducted byresearchers. The results show that the use of learningresources is in the form of using smartphone or laptopor computer applications, namely WhatsApp, GoogleMeet and Google Classroom. As well as the use ofyoutube videos for the needs of student learningmaterials. As well as the use of the lecture methodwhich is deemed appropriate to the implementation ofonline learning. The obstacle experienced by teachersduring online learning lies in the use of applicationsin the early stages of implementing online learning